Linking Knowledge Creation with Employee Engagement: A Conceptual Model - Liu, Yao; Sui, Hai Juan (2017)
Employee engagement is increasingly important in this competitive society because organizational competitive advantage requires knowledge especially the tacit which resides in employees and this cannot be achieved unless employees are engaged in the process of knowledge creation. However, researches have rarely explored to bridge engaging employees with creating knowledge. This paper after reviewing relevant literatures on knowledge creation and employee engagement, emphasized the essential linkage between knowledge creation and employee engagement. It is expected to enhance theory that knowledge creation link to employee engagement. Hopefully, the proposed model could help organizations to understand how employee engagement can be a key approach to achieve competitive advantage through knowledge creation.